"Hoy escribiré una carta": The news of siege warfare in Calderón's El sitio de Bredá. Issue 1 (2nd January 2021) - Oechler, Christopher C.
Abstract: Ambrogio Spinola's victory at the Siege of Breda (1624–1625) marked a high point in the imperial policies of Philip IV and his royal favorite, the Count-Duke of Olivares. Contemporary newsletters celebrated the achievement, and Pedro Calderón de la Barca followed these reports in commemorating the victory in his play El sitio de Bredá (1625). I find that in addition to the obvious praise of the triumphant Habsburg forces and monarchy, El sitio de Bredá cultivates a new vision of imperial siege warfare, one that is nurtured by a preoccupation with the burgeoning news industry. Cueing off contemporary reports, Calderón proposes a recently proven model in juxtaposition with those found in earlier siege plays, specifically El asalto de Mastrique por el Príncipe de Parma by Lope de Vega and Tragedia de Numancia by Miguel de Cervantes. When read alongside these works, Calderón's play suggests an evolution in the depiction of Spanish warfare, redefining its technical and tactical aspects in light of the growing news industry and its rapid dissemination of knowledge.